Advancing environmental education practice - Krasny, Marianne E., (Cornell studies in environmental education., 2020)
"Environmental education can foster behavior change and collective action by going beyond knowledge and attitudes to consider efficacy, identity, sense of place, social capital, nature connectedness, norms, and nudges"--